2022
DOI: 10.1093/nar/gkac918
|View full text |Cite
|
Sign up to set email alerts
|

RNA cytometry of single-cells using semi-permeable microcapsules

Abstract: Analytical tools for gene expression profiling of individual cells are critical for studying complex biological systems. However, the techniques enabling rapid measurements of gene expression on thousands of single-cells are lacking. Here, we report a high-throughput RNA cytometry for digital profiling of single-cells isolated in liquid droplets enveloped by a thin semi-permeable membrane (microcapsules). Due to the selective permeability of the membrane, the desirable enzymes and reagents can be loaded, or re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Semi-permeable hydrogels [ 28 ] or microcapsules [ 29 ] are another state-of-the-art approach for controlling the biochemical reactions within micro-compartments. In these systems, the different reagents smaller than the pore size can diffuse into micro-compartments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-permeable hydrogels [ 28 ] or microcapsules [ 29 ] are another state-of-the-art approach for controlling the biochemical reactions within micro-compartments. In these systems, the different reagents smaller than the pore size can diffuse into micro-compartments.…”
Section: Resultsmentioning
confidence: 99%
“…The peptide concentration increased only slightly to 34 nM when the incubation was continued for a total of 24 h (Figure S3), which suggested that the peptide delivery was mostly completed in the first 3 h. These results demonstrated the feasibility of using nanodroplets to achieve delivery of medium-sized biomolecules into water-in-fluorinated-oil microdroplets. Semi-permeable hydrogels [28] or microcapsules [29] are another state-of-the-art approach for controlling the biochemical reactions within micro-compartments. In these systems, the different reagents smaller than the pore size can diffuse into micro-compartments.…”
Section: Peptide Delivery and Confirmation Using A Fluorescent Immuno...mentioning
confidence: 99%
“…The first applications of hollow microparticles have been the selection of cells based on growth, RNA cytometry, drug delivery, cell delivery, , water treatment, and enzymatic analysis . Atrandi Biosciences has commercialized instruments and microfluidic kits for sequencing microbes using hollow shell particles .…”
Section: Evolution Of Hydrogels For Cell Encapsulationmentioning
confidence: 99%
“…Researchers have devised various compartmentalization methods, such as microwells or homogeneous polymer beads, to enable an open yet isolated system for massively parallel biochemical reactions. [11][12][13] Hydrogel, a biocompatible and inherently porous material, has been extensively used to house biomolecules and cells. [14,15] Hydrogel-based compartments create a permeable environment, enabling the necessary substance exchange for biochemical reactions and cell growth.…”
Section: Introductionmentioning
confidence: 99%